Penggunaan Kalimat Efektif Pada Soal Latihan dalam Buku Paket Bahasa Indonesia SMP Kelas VII Karya Mariati Nugroho dan Sutopo - Kusmiyati, Indri, Drs. Andi Haris Prabawa, M.Hum (2016)
This study aimed to describe the forms of effective use of the phrase, a sentence less effective, and punctuation improper practice questions in textbooks Indonesian junior class VII Mariati paper and Sutopo Nugroho. The method used in this research is descriptive qualitative method. The data in this study is a matter of practice. Sources of data in this research is the textbook Indonesian junior class VII Mariati paper and Sutopo Nugroho. The data collection technique used is the classification of the data, then the data is analyzed by composing a sentence less effective become effective sentence. Based on the analysis, it is known that the use of effective sentence on exercises in textbooks Indonesian Mariati work class VII and Sutopo Nugroho is only mentioned 13 data alone. However, the data is already covering 13 and represents some kind of effective sentence. The use of the phrase less effective in practice questions in textbooks junior class VII works Mariati Nugroho and Sutopo number 45, ie in terms of harmony, there are 6 of data, in terms of effectiveness, there were 24 of data, in terms of kebervariasian there are 4 records, in terms of accuracy are 7 data, and in terms of brevity there are 4 records. Meanwhile, the use of punctuation improper number 17, which is 12 data errors in punctuation (!), 4 the data errors in punctuation (,), and 1 of data errors in punctuation (,) and (!). Keywords: effective sentence, the sentence is less effective, punctuation, exercises